Settlement, subsistence, and change among the Labrador Inuit : the Nunatsiavummiut experience - Felt, Larry, 1943-; Procter, Andrea H., 1974-; Natcher, David C., 1967- (Contemporary studies on the North ;, 2012)
"On January 22, 2005, Inuit from communities throughout northern and central Labrador gathered in a school gymnasium to witness the signing of the Labrador Inuit Land Claim Agreement and to celebrate the long-awaited creation of their own regional self-government of Nunatsiavut. This historic Agreement defined the Labrador Inuit settlement area, beneficiary enrollment criteria, and Inuit governance and ownership rights.